Confirmation of Japanese encephalitis as an endemic human disease through sentinel surveillance in Indonesia - Ompusunggu, Sahat; Hills, Susan L; Maha, Masri Sembiring; Moniaga, Vanda A; Susilarini, Ni Ketut; Widjaya, Anton; Sasmito, Agus; Suwandono, Agus; Sedyaningsih, Endang R; Jacobson, Julie A (The American journal of tropical medicine and hygiene, 2008)
Japanese encephalitis (JE) results in significant mortality and disability in children in Asia. In Indonesia, despite recognition of JE virus transmission, reports of human disease have been few and from limited geographic areas. Hospital-based surveillance for acute encephalitis syndrome (AES) and JE in children 15 years of age and under was undertaken in 15 hospitals in six provinces from 2005 to 2006. High- and low-risk provinces in geographically dispersed areas were included. Health center-based surveillance also was undertaken in one province. Eighty-two JE cases were confirmed among 1,496 AES cases detected. JE cases were confirmed in all provinces, but the proportion varied between 18% and 2% among provinces of different risk levels. Children younger than 10 years of age represented 95% of JE cases, and 47% of all cases either died or were disabled. The study shows JE is an endemic human disease across Indonesia. Immunization strategies are being considered.